2006
DOI: 10.2114/jpa2.25.59
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Maximal Jumps on Sand

Abstract: The purpose of this study was to comparatively investigate the energy expenditure of jumping on sand and on a firm surface. Eight male university volleyball players were recruited in this study and performed 3 sets of 10 repetitive jumps on sand (the S condition), and also on a force platform (the F condition). The subjects jumped every two seconds during a set, and the interval between sets was 20 seconds. The subjects performed each jump on sand with maximal exertion while in the F condition they jumped as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
3
18
0
2
Order By: Relevance
“…In our study, group S achieved greater improvements during and after the 10-week training program in all tested variables (aerobic capacity, agility, jumping and sprinting ability) compared with both groups H and C. Differences caused on biomechanical variables as well as energy expenditure during human locomotion on sand surface have been examined previously [36,37]. The instability of a non-solid ground, like sand, can result in reductions in maximum produced force during squat jump compared to force produced during jumping on rigid surface [2].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In our study, group S achieved greater improvements during and after the 10-week training program in all tested variables (aerobic capacity, agility, jumping and sprinting ability) compared with both groups H and C. Differences caused on biomechanical variables as well as energy expenditure during human locomotion on sand surface have been examined previously [36,37]. The instability of a non-solid ground, like sand, can result in reductions in maximum produced force during squat jump compared to force produced during jumping on rigid surface [2].…”
Section: Discussionsupporting
confidence: 50%
“…The ankle-, kneeand hip joint kinematics are altered because of sand instability implying altered demands on the neuromuscular system [2,38]. Furthermore sprinting and jumping on sand surface seems to decrease significantly stride length, because of loss of energy during acceleration, leading in a larger number of surface contacts in order to cover the same distance [36][37][38]. Gaudino et al, (2013) [36] reported also that running on sand surface increases the energy cost by 30% compared with the values achieved during running on grass surface.…”
Section: Discussionmentioning
confidence: 99%
“…They have explained this inconsistency by differences in surface construction because their -----subjects mentioned a sensation of "running on sand" indicating that the surface may have had too much damping or inertia to effectively produce a "rebound" effect as in other surfaces used. Indeed, running on sand increases energy expenditure compared to running on hard surfaces [29,38,40], grass [37] and force platform [35] because sand doesn't return energy absorbed in the earlier phase of each step and, thus, this lost energy must be replaced by the muscles' activities at later phase of each step [10,29]. This is also true for jumping on the surfaces with very high shock absorption other than sand [16,33].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that the period of exercise of the study was short and the exercise was consisted of a single exercise, thus there was no difference between groups. Furthermore, there were studies that reported that exercising on sand surfaces induced more fatigue and energy expenditure after exercise than other surfaces [25,26]. In the study, the balance abilities were measured for one minute after the exercise, thus the participants may not have had enough time to recover from exercising on a sand surface when it was time to perform the SEBT.…”
Section: Discussionmentioning
confidence: 99%